Analisis Tata Kelola Pemerintahan Daerah Pasca Penindakan Korupsi Kepala Daerah - Feren Nur Jayanti; Dian Suluh Kusuma Dewi (Journal of Governance Innovation, 2026)
The prosecution of corruption cases involving regional heads remains a recurring issue in Indonesia and affects governmental stability and local governance quality. This article aims to analyze local governance conditions after corruption prosecution, using Ponorogo Regency as a case study following the designation of Regent Sugiri Sancoko as a suspect by the Corruption Eradication Commission. This study employs a qualitative descriptive case study approach based on literature review and document analysis. The findings show that corruption prosecution leads to leadership transition, changes in bureaucratic dynamics, and increased public demands for transparency and accountability. However, post-prosecution governance still faces structural challenges, including weak internal oversight, limited human resource capacity, and policy uncertainty. Therefore, legal enforcement should be accompanied by systemic governance improvements.